2023
DOI: 10.1155/2023/5068304
|View full text |Cite
|
Sign up to set email alerts
|

Rutin and Hesperidin Alleviate Paclitaxel‐Induced Nephrocardiotoxicity in Wistar Rats via Suppressing the Oxidative Stress and Enhancing the Antioxidant Defense Mechanisms

Abstract: Paclitaxel is a primary chemotherapy agent that displays antitumor activity against a variety of solid tumors. However, the clinical effectiveness of the drug is hampered by its nephrotoxic and cardiotoxic side effects. Thus, this investigation aimed at assessing the protective effects of rutin, hesperidin, and their combination to alleviate nephrotoxicity caused by paclitaxel (Taxol), cardiotoxicity in male Wistar rats, as well as oxidative stress. Rutin (10 mg/kg body weight), hesperidin (10 mg/kg body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 81 publications
1
5
0
Order By: Relevance
“…Numerous authors have confirmed a favorable association between plant phenolic content and antioxidant function (Ali, Ahmed, et al, 2023;Ali, Cottrell, & Dunshea, 2023;Souilah et al, 2021).…”
Section: Antioxidant Capacitymentioning
confidence: 92%
“…Numerous authors have confirmed a favorable association between plant phenolic content and antioxidant function (Ali, Ahmed, et al, 2023;Ali, Cottrell, & Dunshea, 2023;Souilah et al, 2021).…”
Section: Antioxidant Capacitymentioning
confidence: 92%
“…3. Arthritic treated (H) group: RA rats received the quercetin suspension at a dosage of 15 mg/kg 13,14 and normal NaCl solution and a routine diet. 4.…”
Section: X-ray Diffractometry (Xrd)mentioning
confidence: 99%
“…Therapeutic efficacy of the prepared SLNs was assessed by testing ankle swelling, 13 biochemical and inflammatory biomarker levels, 5 and histopathological analysis of the ankle joint. 14 Statistics. The data for the blood parameters were compared using one-way ANOVA using p < 0.05.…”
Section: X-ray Diffractometry (Xrd)mentioning
confidence: 99%
See 1 more Smart Citation
“…These include reducing cell migration and exhibiting anticancer activity [7,8]. Artichoke leaf and head extract has been shown to lower lipid levels and protect the intestine from inflammation and oxidative factors [9,10,11]. Furthermore, it has a hepatoprotective effect in a high-fat diet rat model [12].…”
Section: Introductionmentioning
confidence: 99%